Value of Fluoro-2-Deoxy-D-Glucosefluoro-2-Deoxy-D-Glucose Positron Emission Tomography/Computed Tomography in Symptomatic and Asymptomatic Tuberculosis - Akgün, Elife; Akyel, Reşit (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this retrospective study is to evaluate the difference of 18-fluorine fluoro-2-deoxy-d-glucose positron emission tomography/ computed tomography images between the symptomatic and asymptomatic tuberculosis cases. Methods: Patients diagnosed with tuberculosis underwent 18-fluorine fluoro-2-deoxy-d-glucose positron emission tomography/computed tomogra- phy imaging. Cases were categorized according to symptom status, types/number of symptoms, types/localization of lung lesions, and extrapulmonary involvement sides. Every lesion with pathologic features on computed tomography and/or increased 18-fluorine fluoro-2-deoxy-d-glucose uptake was measured semiquantitatively using the maximum standardized uptake value. Results: One hundred fourteen patients (n = 40 female, n = 74 male; median age 57) were enrolled in this study. Although lung parenchyma involve- ment was observed significantly at a higher rate in males than females, pleural and lymph node involvement was revealed at significantly higher rates in females. No significant difference was found between the symptom-positive and -negative groups in terms of gender, localization/types of lung lesion, and extrapulmonary involvement sides detected with positron emission tomography/computed tomography. Based on the criteria of maximum standardized uptake value greater than 2.0 to define active lesions, 9.5% of symptomatic cases had inactive lesions, while 80% of asymptomatic cases had active lesions. There was no statistically significant difference between the maximum standardized uptake value values of the types of lung lesions. While a positive low correlation was detected between maximum standardized uptake value of lung parenchymal lesions and the number of symptoms, a negative moderate correlation was found between the maximum standardized uptake value values of the pleura and the age. Conclusion: Interestingly, there was no significant difference between symptomatic and asymptomatic tuberculosis cases in terms of types of lung lesions and extrapulmonary involvement sides. The majority of the asymptomatic cases had active disease. Based on the findings, we think that 18-fluorine fluoro-2-deoxy-d-glucose, positron emission tomography/computed tomography is a valuable imaging modality even in asymptomatic cases with a low probability of clinically active tuberculosis. Cite this article as: Akgün E, Akyel R. Value of 18-fluorine fluoro-2-deoxy-d-glucose–positron emission tomography/computed tomography in symptomatic and asymptomatic tuberculosis. Cerrahpaşa Med J. 2023;47(2):141-149.